PREDICTORS OF JOB SATISFACTION AMONG PRIVATE SECTOR INDUSTRY WORKERS IN PORT HARCOURT, RIVERS STATE: FUNCTION OF SELFESTEEM AND JOB STRESS - Sydney-Agbor, Ngozi (African Journal of Social and Behavioural Sciences, 2020)
This study investigated the contributions of self-esteem and job stress to job satisfaction among private sector employees in Port Harcourt, Rivers State. Participants comprise of 374 workers selected from Mandilas, Alcon Ltd, Anadrill Schlumberger and First Aluminium through convenience sampling. The participants consist of 217 male and 157 female employees whose ages ranged from 25 to 51 and a mean age of 40.8. Three instruments were administered to these participants: Index of Self-esteem (ISE)), Minnesota Satisfaction Questionnaires (MSQ) and HSE (Health and Safety Executive) Management Standards Indicator Tool, Descriptive survey design was adopted and Multiple Regression Analysis was used to analyze data collected. Results showed that low self-esteem and job stress positively predicted job satisfaction (p<.05). Implications of this study are that when the expectation of a worker is less, job satisfaction can be attained, and minimal stress can be motivating which can increase job satisfaction.